Prognostic Value of Body Mass Index Stratified by Alcohol Drinking Status in Patients With Esophageal Squamous Cell Carcinoma - Chen, Shao-bin; Liu, Di-tian; Chen, Yu-ping (Frontiers in Oncology, 2022)
Background: The goal of this study was to investigate the prognostic value of body mass index (BMI) in patients with esophageal squamous cell carcinoma (ESCC) when stratified by alcohol drinking status. Methods: A total of 620 patients with ESCC who underwent esophagectomy were analyzed. A receiver operating characteristic curve was constructed to set the appropriate cutoff point for BMI. Alcohol drinking was divided into ever and never. Kaplan-Meier and multivariate Cox regression analyses were conducted to investigate the association between clinicopathological factors and survival. Results: The cutoff point was 18.75 kg/m2 for BMI. Two hundred and twenty-nine patients were ever drinkers, while the other 391 patients were never drinkers. The ever drinker group was found to have more males, longer tumor lengths, advanced pT category disease, advanced pN category disease, and lower tumor locations. However, no significant difference in BMI was found between ever drinkers and never drinkers. For ever drinkers, low BMI was significantly correlated with worse overall survival (hazard ratio = 1.690; P=0.035) and cancer-specific survival (hazard ratio = 1.763; P=0.024) than high BMI after adjusting for other factors. However, BMI was not a prognostic factor in univariate and multivariate analyses for never drinkers. Conclusions: BMI is a prognostic factor only in ever drinkers with ESCC but not in never drinkers. Further studies are needed to elucidate the mechanism underlying the effect of the interaction between BMI and alcohol consumption on the prognosis of patients with ESCC.